Pulmonary mucormycosis with bacterial coinfection in an adolescent with poorly controlled type 1 diabetes: a case report - Rong, Fu; Mingying, Zhang; Ying, Bai; Yiyun, Huang; Ying, Qian; Zheng, Xing; Xiaolei, Chu (Frontiers in Endocrinology, 2026)
BackgroundPulmonary Mucormycosis (PM), a severe fungal infection affecting mainly immunocompromised individuals, is often caused by fungi like Rhizopus and Mucor. This report details a 12-year-old diabetic girl with pulmonary mucormycosis from an unusual Rhizopus species. Successful treatment involved stabilizing her blood glucose and managing multiple co-infections. This case provides important insights into diagnosing and treating rare fungal infections in diabetic children.Case summaryA 12-year-old girl with a two-year history of type 1 diabetes, inconsistently monitored, was hospitalized. She had a persistent cough for over ten days and a six-day high fever. Previous treatments with dexamethasone and antibiotics were ineffective. She showed symptoms of a productive cough, right-sided pleuritic chest pain, and a fever of 40°C. Examination revealed reduced breath sounds and moist rales in the right lung. Tests confirmed a severe infection, and imaging showed inflammatory consolidation, multiple cavitations, and pleural effusion in the right lung.DiagnosisMetagenomic next-generation sequencing (mNGS) analyzes all nucleic acids from a patient’s bronchoalveolar lavage fluid to identify various pathogens without traditional cultures. The analysis identified Rhizopus species and Streptococcus pneumoniae, confirming pulmonary mucormycosis with a bacterial infection. Additionally, the glycated hemoglobin (HbA1c) level was 14.3%, indicating poorly controlled diabetes.TreatmentA comprehensive treatment regimen was employed. The bacterial co-infection was addressed with intravenous administration of meropenem and linezolid, while nebulized amphotericin B was utilized to treat the pulmonary mucormycosis. To mitigate the underlying risk factor, intensive glycemic control was achieved through the use of an insulin pump. Furthermore, bronchoscopy was conducted to clear respiratory secretions.OutcomeAfter 11 days in the hospital, the patient stabilized and was discharged. At a follow-up 1.5 months later, infection markers and blood glucose levels were normal.ConclusionThis case highlights the high risk of severe infections like pulmonary mucormycosis in adolescents with poorly managed type 1 diabetes. Metagenomic sequencing was crucial for quickly identifying co-infections. Successful treatment required a comprehensive approach, including targeted antimicrobial therapy, strict glycemic control, and bronchoscopic support, leading to a positive outcome.